BMP4 and LGL1 are Down Regulated in an Ovine Model of Congenital Diaphragmatic Hernia - Emmerton-Coughlin, Heather M. A.; Martin, K. Kathryn; Chiu, Jacky S. S.; Zhao, Lin; Scott, Leslie A.; Regnault, Timothy R. H.; Bütter, Andreana (Frontiers in Surgery, 2014)
Background/Purpose: The molecular pathophysiology of lung hypoplasia in congenital diaphragmatic hernia (CDH) remains poorly understood. The Wnt signaling pathway and downstream targets, such as bone morphogenetic proteins (BMP) 4 and other factors such as late gestation lung protein 1 (LGL1), are essential to normal lung development. Nitrofen-induced hypoplastic CDH rodent lungs demonstrate down regulation of the Wnt pathway including BMP4 and reduced LGL1 expression. The aim of the current study was to examine the molecular pathophysiology associated with a surgically induced CDH in an ovine model. Methods: Left thoracotomy was performed at 80 days in 14 fetal sheep; CDH was created in seven experimental animals. Lungs were harvested at 136 days (term = 145 days). Lung weight (LW) and mean terminal bronchiole density (MTBD) were measured to determine the degree of pulmonary hypoplasia. Quantitative real time PCR was undertaken to analyze Wnt2, Wnt7b, BMP4, and LGL1 mRNA expression. Results: Total LW was decreased while MTBD was increased in the CDH group (p < 0.05), confirming pulmonary hypoplasia. BMP4 and LGL1 mRNA was significantly reduced in CDH lungs (p < 0.05). Wnt2 mRNA was decreased, although not significantly (p < 0.06). Conclusion: For the first time, down regulation of BMP4 and LGL1 are reported in an ovine CDH model. In contrast to other animal models, these changes are persistent to near term. These findings suggest that mechanical compression from herniated viscera may play a more important role in causing pulmonary hypoplasia in CDH, rather than a primary defect in lung organogenesis.